Current Evidence and Future Perspectives on the Effective Practice of Patient-Centered Laboratory Medicine. (6th January 2020) - Hallworth, Mike J; Epner, Paul L; Ebert, Christoph; Fantz, Corinne R; Faye, Sherry A; Higgins, Trefor N; Kilpatrick, Eric S; Li, Wenzhe; Rana, S V; Vanstapel, Florent
Abstract: BACKGROUND: Systematic evidence of the contribution made by laboratory medicine to patient outcomes and the overall process of healthcare is difficult to find. An understanding of the value of laboratory medicine, how it can be determined, and the various factors that influence it is vital to ensuring that the service is provided and used optimally. CONTENT: This review summarizes existing evidence supporting the impact of laboratory medicine in healthcare and indicates the gaps in our understanding. It also identifies deficiencies in current utilization, suggests potential solutions, and offers a vision of a future in which laboratory medicine is used optimally to support patient care. SUMMARY: To maximize the value of laboratory medicine, work is required in 5 areas: ( a ) improved utilization of existing and new tests; ( b ) definition of new roles for laboratory professionals that are focused on optimizing patient outcomes by adding value at all points of the diagnostic brain-to-brain cycle; ( c ) development of standardized protocols for prospective patient-centered studies of biomarker clinical effectiveness or extraanalytical process effectiveness; ( d ) benchmarking of existing and new tests in specified situations with commonly accepted measures of effectiveness; ( e ) agreed definition and validation of effectiveness measures and use of checklists for articles submitted for publication. Progress in these areas is essential if we are to demonstrate and enhance the value of laboratory medicine and prevent valuable information being lost in meaningless data. This requires effective collaboration with clinicians, and a determination to accept patient outcome and patient experience as the primary measure of laboratory effectiveness.